(untitled) (Confluenţe Bibliologice, 2013)
The article reflects the long-standing relationship and fruitful collaboration between the author and the Scientific Library of the "A. Russo" University in Balti. The text highlights the importance of the library as a space for professional support, promotion of reading, and preservation of local cultural heritage.